Game Edukatif pada Materi Teks Wawancara untuk Mendukung Literasi Membaca Siswa Sekolah Dasar - Ragil Dian Purnama Putri; Wiwik Kusuma; Tri Lestari (Jurnal Teknologi Informasi dan Multimedia, 2026)
This study aims to develop an educational game-based learning media using Smart Apps Creator 3, named “SIMAKA,” to support elementary school students’ reading literacy in interview text materials. The method used is Research and Development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Data collection techniques involve validation questionnaires and user responses, which are analyzed quantitatively in descriptive form using percentages. The results show that the media achieved a feasibility level of 92.8% from experts, 95% from teachers, and 93% from students, all categorized as very good. These findings indicate that the developed media is feasible to be used as an alternative learning tool to support students’ reading literacy.